Reconceptualising education in Sub-Saharan Africa : realising equity and social justice - Aluko, F. R.; Omidire, M. F.; Mampane, M. R. (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
Although the sub-Saharan Africa region has made giant strides in education, the quality still requires improvement. Linked to this is the high unemployment rate among youth, which has led to migration, with dire consequences. Apart from training people to be literate and numerate, education prepares individuals for life. In this article, the authors present teachers’ ideas on a proposed conceptual framework that synthesises the current education system with the traditional African system of education and training. To capture the complexity of the challenge and evaluate its relevance, the authors have adopted the Capabilities Approach Theory, using the explanatory sequential mixed-methods approach. The main research question that guided this study is: “To what extent is the evidence-based conceptual framework feasible for the reconceptualisation of education in the sub-Saharan Africa region, and what are the implications of the findings for education in this and similar contexts? Purposively selected participants made up a sample of 200 teachers for the survey and 10 teachers for the focus group discussion. Data analysis involved descriptive and thematic analysis. Findings revealed that all participants agreed on the need to reconceptualise education in the region and complimented the suggested framework. However, ideas were divergent on how to implement the reconceptualisation of education. The study recommends the need for an African formal education curriculum to be functional, and to focus more on contextualised skills training and job creation, among other things.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022)
Keywords: Education systems; Sub-Saharan Africa; Social justice; Capabilities approach; Teaching; Social justice; Total quality management in education; Social justice and education